Simultaneous Imaging of Cerebrovascular Structure and Function in Hypertensive Rats Using Synchrotron Radiation Angiography - Wang, Liping; Mu, Zhihao; Lin, Xiaojie; Geng, Jieli; Xiao, Ti Qiao; Zhang, Zhijun; Wang, Yongting; Guan, Yongjing; Yang, Guo-Yuan (Frontiers in Aging Neuroscience, 2017)
Hypertension has a profound influence on the structure and function of blood vessels. Cerebral vessels undergo both structural and functional changes in hypertensive animals. However, dynamic changes of cerebrovasculature and the factors involved in this process are largely unknown. In this study, we explored the dynamic changes of vascular structure in hypertensive rats using novel synchrotron radiation angiography. 24 spontaneously hypertensive rats (SHR) and 24 Sprague–Dawley (SD) rats underwent synchrotron radiation (SR) angiography. We studied the cerebral vascular changes in SHR over a time period of 3 to 12-month and performed quantitative analysis. No vascular morphology differences between SHR and SD rats were observed in the early stage of hypertension. The number of twisted blood vessels in the front brain significantly increased at the 9- and 12-month observation time-points in the SHR compared to the SD rats (p<0.01). The vessel density of the cortex and the striatum in SHR was consistently higher than that in SD rats at time points of 3-, 9- and 12- month (p<0.001). Vascular elasticity decreased both in SHR and SD rats with aging. There were statistically significant differences in the relative vascular elasticity of extracranial/intracranial internal carotid artery, middle cerebral artery, posterior cerebral artery and anterior cerebral artery between SHR and SD rats at 12-month (p<0.01). We concluded that the dynamic vascular alterations detected by SR angiography provided novel imaging data for the study of hypertension in vivo. The longer the course of hypertension was, the more obvious the vascular differences between the SHR and the SD rats became.